Development of Software for Duval Triangle and Pentagon Interpretation on Transformer Oil Dissolved Gas Analysis - Abdul Latiff, Zukry; Mohd Yousof , Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2021)
Duval triangle (DT) and Duval pentagon (DP) are methods to interpret the dissolved gas analysis (DGA) result of transformer oil. DGA is used to differentiate between normal and fault condition of the power transformer as it require a high degree of reliability. This is because any fault that occurred to the unit will bring a huge impact on power transmission system. Since transformers are in operation continuously, it is very important to avoid any accident by able to predict faults within them and conducting maintenance on the transformer’s condition. DT utilized concentration of three gases from the DGA. On the other hand, DP utilized concentration of five gases. These concentrations are then interpreted by DT and DP methods. The interpretation would identify which fault occurs. This paper presents a comparison on the outcome of DT and DP analysis. The analysis is then presented in a standalone graphical user interface (GUI) software. Three case studies were presented based on three different transformers’ DGA samples. The first cases gave out the same result for DT and DP interpretation. However, the other two cases had some differences in the result interpretated. The differences were shown in the result and discussion.